Does taper water boil at all temperatures? - Andrade Gamboa, Julio José; Donati, Edgardo Ruben (Universidad Nacional Autónoma de México. Facultad de Química, 2021)
Fil: Andrade Gamboa, Julio José. Universidad Nacional del Comahue. Centro Regional Universitario Bariloche; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina